THE GOLDEN RULE FOR CAREER CHOICES: A CONTEMPORARY APPROACH TO APPLIED CAREER COUNSELLING - Theodore Katsanevas; Ioanna Tsiaparikou (European Scientific Journal, ESJ, 2014)
Career counselling will be analysed in an interdisciplinary and holistic manner focussing on the common denominators between the psychology of work and labour economics. In an attempt to develop valid guidelines for applied career counselling, we will concentrate upon basic critical factors that influence career choices, such as: personality interests, abilities and will, labour market, family and financial data, random events. All the above factors interact with each other under the umbrella of the so-called “golden rule for career choices”, an original approach introduced in this paper. Basic assumption of this notion is that persons with great abilities and strong will have their choice of a wider range of professions that match with their personality type, including professions not comprising other positive factors. Conversely, people with subpar abilities and a weak will would be advised to choose professions that firstly match their personality and secondly, include positive factors mentioned above.